Education on Kegel Exercises as an Effort to Accelerate Healing of Perineal Wounds in Postpartum Mothers at the Driyorejo Gresik Community Health Center - Reni Yuli Astutik; Mei Ringga Peni Santiana; Retno Palupi Yonni Siwi; Devy Putri Nursanti (Journal of Community Engagement in Health, 2024)
Infections in the postpartum period are caused by delays in perineal wound healing. Kegel exercises are exercises to strengthen the pelvic floor muscles, help prevent urinary incontinence problems, and can stretch the perineal tissue as the baby's birth canal. Accelerate healing of perineal wounds in postpartum mothers at the Driyorejo Gresik Community Health Center through Kegel exercise education. This community service was carried out on postpartum mothers with perineal wounds in the Driyorejo Gresik Community Health Center working area in March 2024. The number of postpartum mothers who were given Kegel exercises was 30 people. Service activities are divided into 3 stages, namely preparation, implementation and evaluation. The results of the activity showed a decrease in REEDA scores after doing Kegel exercises. Giving Kegel exercises can speed up the healing of perineal wounds. Kegel exercises given to postpartum mothers for 7 days and done 3 times a day with movements that activate the pubococcygeal muscles can improve blood and oxygen circulation to the muscles and tissues around the perineum.